The Alignment of Interpersonal Text Language Functions in Podcasts with the Standard Competence of English Language for Junior High School - Ardani, Hanun Nisrina; Agustina, Imas Wahyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2022)
This study aims to analyze the alignment of the interpersonal text language functions that occurred in podcasts with the standard competence of the 2013 curriculum to teach interpersonal texts for Junior High School. This research is a descriptive qualitative study using the content analysis method. The study is based on KI (Kompetensi Inti)/KD (Kompetensi Dasar) in Kurikulum 2013 proposed by the Indonesian Ministry of Education and Culture (2018) as the analysis framework to analyze the type of language function and expressions of interpersonal text used in the 15 podcasts. The result shows that all 15 podcasts provide 18 out of 21 language functions required in the standard competence of Interpersonal texts at the Junior High level. The language functions occurring in all podcasts cover Greeting, Leavetaking, Extending Invitations, Expressing Gratitude, Complimenting, Asking for Attention, Asking for Opinions, Expressing Opinions, and so on. It means the podcasts fulfilled 85,7% of the standard competence and can be used as teaching materials to teach interpersonal text for Junior High School students.